Women's (Community) Radio as a Feminist Public Sphere - Mitchell, Caroline (Javnost-The Public, 1998)
This article explores how women's community radio can contribute to a “feminist public sphere” and serve as a tool for women's empowerment through the media. Compared to film, TV and newspapers, radio is a relatively under researched and under valued area of the media. An extension of this situation is the paucity of theoretical and empirical studies regarding women and radio. The purpose of this article is to contribute to a theory of women’s radio and its relation to practice. Employing feminist “readings” of Habermas' theory of the public sphere, it is possible to develop a concept of a women's or feminist public sphere in relation to women’s community radio. This article discusses whether and how this is emerging through the opportunities that women have in terms of access, training and development in community radio. With empirical data from women's radio stations and projects in different parts of Europe, radio as a potential “feminist public sphere” is explored, and a foundation laid for a further grounding of an understanding of how alternative media can be a tool for women's empowerment.